1987
DOI: 10.1111/j.1600-9657.1987.tb00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial pulpotomy as a treatment alternative for exposed pulps in crown‐fractured permanent incisors

Abstract: Sixty‐three vital permanent incisors with complicated crown fractures were treated by partial pulpotomy and assessed clinically and radiographically for healing. Healing of the pulp was considered to have taken place when the following criteria were fulfilled: absence of clinical symptoms, radiographic evidence of dentin bridge formation, no intrapulpal or periapical pathosis, continued root development in immature teeth, and a positive response to electrical pulp testing. The treatment was successful in 59 te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 8 publications
0
52
1
1
Order By: Relevance
“…Partial pulpotomy is indicated in mature and immature teeth showing vital pulp tissue at the exposure site, irrespective of its size and interval between injury and treatment [16]. This technique is regarded as the treatment of choice for pulp exposures > 2 mm or where the patients present as late as 24 h after the injury [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Partial pulpotomy is indicated in mature and immature teeth showing vital pulp tissue at the exposure site, irrespective of its size and interval between injury and treatment [16]. This technique is regarded as the treatment of choice for pulp exposures > 2 mm or where the patients present as late as 24 h after the injury [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…It was of some concern that a substantial number of the teeth treated became nonvital, in view of the successful healing rates recorded for the use of pulp treatment techniques elsewhere [4, 5, 9, 10]. However, the time taken to become nonvital was important.…”
Section: Discussionmentioning
confidence: 99%
“…Histological observations of healed pulps electively extirpated in 14–19‐year‐olds for restorative reasons, 12–95 months after partial pulpotomies had been carried out, have suggested that routine use of a pulpectomy after partial pulpotomy of exposed vital pulps does not appear to be justified [7]. In addition, the area of exposed pulp tissue and the interval between accident and treatment do not appear to be critical for the healing of a primarily healthy pulp providing the superficially inflamed tissue is removed and the technique used minimizes injury to the remaining pulp [8–10]. Overall, a more cautious approach in the management of teeth with vital pulps appears to be justified, aiming to retain pulp vitality if possible, with elective root canal therapy deferred until late adolescence when apexification is complete and the root canal has attained a more mature configuration.…”
Section: Introductionmentioning
confidence: 99%
“…11 Fuks AB ve ark. 'nın, 21 komplike kron kırığı nedeniyle pulpası açılmış olan 63 tane daimi keser dişte uygulamış olduğu parsiyel pulpatomi tedavisi sonrasında; 59 dişte herhangi klinik ve radyolojik patoloji bulgusuna rastlanmadığı, elektrikli pulpa testlerine pozitif yanıt alındığı ve radyografik olarak dentin köprüsü oluştuğu görülürken sadece 4 dişte nekroz bulgularına rastlandığı bildirilmiştir. Böylece parsiyel pulpatomi tedavisinin yüksek klinik ve radyolojik başarı gösterdiği rapor edilmiştir.…”
Section: ) Parsiyel Pulpatomi (Cvek Amputasyonu)unclassified